2014
DOI: 10.1115/1.4025823
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow and Heat Transfer in a Novel Microchannel Heat Sink Partially Filled With Metal Foam Medium

Abstract: Performance of microchannel heatsink (MCHS) partially filled with foam is investigated numerically. The open cell copper foams have the porosity and pore density in the ranges of 60–90% and 60–100 PPI (pore per inch), respectively. The three-dimensional steady, laminar flow, and heat transfer governing equations are solved using finite volume method. The performance of microchannel heatsink is evaluated in terms of overall thermal resistance, pressure drop, and heat transfer coefficient and temperature distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In order to study the effects of disturbance in the micro-channels, researchers build turbulent micro structures in the micro-channel, which improve the heat exchange efficiency and realize the consistency of flow rate [ 14 , 15 ]. The liquid working as coolant for micro-channel is also studied, and the heat capacity, thermal conductivity and viscosity all significantly affect the cooling capacity of the micro-channel [ 16 , 17 ]. In addition, the phase change mechanism may be employed to realize a two-phase micro fluid channel heat sink, which further improves its heat dissipation capability [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the effects of disturbance in the micro-channels, researchers build turbulent micro structures in the micro-channel, which improve the heat exchange efficiency and realize the consistency of flow rate [ 14 , 15 ]. The liquid working as coolant for micro-channel is also studied, and the heat capacity, thermal conductivity and viscosity all significantly affect the cooling capacity of the micro-channel [ 16 , 17 ]. In addition, the phase change mechanism may be employed to realize a two-phase micro fluid channel heat sink, which further improves its heat dissipation capability [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such analyses by Hung et al [13,14] indicated that the demerit of high pumping power requirement for flow through microchannels filled with sintered porous material could be alleviated by providing height or width enlargement to the channels. Numerical results of Farsad et al [15] and Shen et al [16] exhibited a more uniform sink temperature profile provided by microchannels partially filled by porous metal foam. Shen et al [16] validated their model against the results of Calmidi and Mahajan [17] for low Re flow through a continuous foam structure.…”
Section: Motivationmentioning
confidence: 91%
“…Microchannel heat sinks filled with metal foam were investigated numerically by E. Farsad et al [15]. Results showed that microchannel heat sinks filled with copper foam could achieve better temperature uniformity.…”
Section: Introductionmentioning
confidence: 99%